2012
DOI: 10.1097/scs.0b013e31825055b1
|View full text |Cite
|
Sign up to set email alerts
|

Surgery-First Approach in Class III Open-Bite

Abstract: Recently, surgical-orthodontic treatment without preoperative orthodontic treatment (known as the surgery-first approach or SFA) has been proposed to improve facial aesthetics from the beginning of treatment, to shorten the entire treatment period, and to take advantage of the regional accelerated phenomenon for orthodontic tooth movement. The SFA concept involves the prediction and simulation of dental alignment, incisor decompensation, and arch coordination using manual setup models. Based on this, decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The 2.5 virtual model surgery (VMS) system combines information of 2D lateral and posteroanterior cephalograms and 3D virtual models. 38 Oh et al 39 reported improved accuracy, reduced cost and duration and complexity, as compared to the manual technique using 2.5 VMS system. Uribe et al 40 and Ima et al 22 utilized the 3D VMS system consisting of 3D imaging technique and virtual models for treatment of subjects with skeletal Class III and facial asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The 2.5 virtual model surgery (VMS) system combines information of 2D lateral and posteroanterior cephalograms and 3D virtual models. 38 Oh et al 39 reported improved accuracy, reduced cost and duration and complexity, as compared to the manual technique using 2.5 VMS system. Uribe et al 40 and Ima et al 22 utilized the 3D VMS system consisting of 3D imaging technique and virtual models for treatment of subjects with skeletal Class III and facial asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies on the SFA have reported relevant cases. Villegas reported the use of SFA in patients with facial asymmetry [20], and Oh et al reported a patient with an open bite treated using the SFA [21]. Wang et al studied the transverse dimensional changes using posteroanterior cephalograms and reported no marked differences between patients treated with the SFA and those treated with the orthodontics-first approach [22].…”
Section: Discussionmentioning
confidence: 99%
“…Formerly, the case with anticipated open bite after surgery would be discouraged by the SFA [7, 27]. However, it had been reported that open bite could be successfully treated by the SFA [31]. Currently, the indication barriers for the SFA are continuously changing and are sometimes overcome by technological advancements.…”
Section: Reviewmentioning
confidence: 99%